Quality of Life and Community Integration of Stroke Survivors Receiving Services from Trained Village Health Volunteers at the Community Rehabilitation Center, Doi Lor Sub-district Administrative Organizations, Doi Lor District, Chiang Mai Province - ชินชัย, พิศักดิ์; คงสวัสดิ์, ศิริพันธุ์; กาบวัง, สุรพงค์; จันทร์ชัย , นิรันดร์ (Journal of Health Science of Thailand, 2022)
The numbers of people with disabilities resulting from stroke are increasing in Thailand. The disease’s main complication was muscle weakness, which causes difficulty with functional ability, poor quality of life (QOL), and discomfort with community integration. Community-based rehabilitation is the strategy that could be used for therapy for these individuals. There were a large number of people with disabilities in Doi Lor sub-district, Doi Lor district, Chiang Mai province. The purpose of the present study, therefore, was to investigate rehabilitation outcomes in areas of QOL and community integration of stroke participants before and 8 weeks after receiving rehabilitation from the trained village health volunteers (VHVs). Eleven stroke subjects were recruited into the study. The following instruments were used: (1) the World Health Organization Quality of Life – short version – Thai (WHOQOL-BREFTHAI); and (2) the community integration questionnaire. Statistics used were the descriptive and Wilcoxon Signed Ranks Test. The results demonstrated that scores of the whole QOL, the physical and the environmental domains of QOL in stroke participants were significantly increased from pretest to post-test (p<0.05). Furthermore, post-intervention scores for the whole community integration and home integration domains in these individuals were significantly higher than pretest scores (p<0.05). This indicated that a community rehabilitation center that is run by the trained VHVs at Doi Lor sub-district administrative organization could promote QOL and community integration in stroke participants who come for their services.